1995
DOI: 10.1177/0265407595123005
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study Marital Interdependence and Social Networks

Abstract: In an exploratory study of 25 wives and their husbands we examine the associations of spouses with kin and friends as predictors of four marital qualities: love, maintenance, conflict and ambivalence. For husbands, contact with kin, and especially fathers, is tied to greater marital interdependence and lower conflict. For wives, contact with kin, and especially brothers-in-law, is consistently associated with greater marital distress in the form of lower love for her husband and reports of greater conflict and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 11 publications
1
71
1
Order By: Relevance
“…Thus, one important result of this study is that contextual unbalance is critical for couple functioning. A likely explanation for this effect is that unicentric networks may increase tensions between spouses in cases of conflict because of unbalanced third parties involvement (Baumgartner, 1993;Burger and Milardo, 1995;Klein and Milardo, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, one important result of this study is that contextual unbalance is critical for couple functioning. A likely explanation for this effect is that unicentric networks may increase tensions between spouses in cases of conflict because of unbalanced third parties involvement (Baumgartner, 1993;Burger and Milardo, 1995;Klein and Milardo, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Because of these variations, it has been hypothesized that network composition (friends versus relatives) has an effect on conjugal outcomes. In an exploratory study, Burger and Milardo (1995) found, for instance, that husbands report greater marital conflict and ambivalence in conjugal relationships when wives interact frequently with friends rather than with relatives.…”
Section: Structural and Functional Characteristics Of Support Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…This general finding was surprising because based on sociological research (e.g. Blood, 1969;Burger & Milardo, 1995) one might have expected complementarity, for example, between closeness with parents and partners. This kind of complementarity at the very beginning of partner relationships has been sometimes called the Romeo and Juliet effect, especially when parental interference was associated with increased romantic love for the dating couple (Driscoll, Davis, & Lipetz, 1972).…”
Section: Social Network Relationships Count Beyond Personalitymentioning
confidence: 94%